Promoting Muhammadiyah Values Through Children's Song in Early Education: Mempromosikan Nilai-Nilai Kemuhammadiyahan Melalui Lagu Anak di Pendidikan Usia Dini - Puspitasari, Kartika; Rochmah, Luluk Iffatur (Journal of Islamic and Muhammadiyah Studies, 2024)
General Background: Singing is a favored activity among early childhood learners, enhancing their learning outcomes. Specific Background: This study presents “Muhammadiyah Gerakan Dakwah,” a children’s song designed to introduce early learners to the principles of Al Islam, Kemuhammadiyahan, and Ke’Aisyiyahan. Knowledge Gap: There is a lack of educational resources that integrate cultural and religious themes suitable for young children. Aims: The aim is to create a musical resource that engages children while educating them about Muhammadiyah and Aisyiyah. Results: The song features simple lyrics and a catchy melody, introducing key figures, symbols, and organizations, thereby facilitating knowledge retention. Novelty: This work provides a culturally relevant tool that combines music with education. Implications: Integrating music into early childhood education can enhance language development and social-emotional growth, offering educators a valuable resource to improve learning outcomes in Muhammadiyah-affiliated schools. Highlights: Enhances Learning: Singing promotes better comprehension and retention of educational content among young learners. Cultural Relevance: The song introduces key figures and symbols of Muhammadiyah and Aisyiyah, fostering cultural awareness. Accessible Resource: Designed with simple lyrics, it provides an engaging tool for educators in Muhammadiyah-affiliated schools. Keywords: Early Childhood, Muhammadiyah, Song, Education, Engagement